BERDIRINYA GEREJA KRISTEN JAWI WETAN (GKJW) TUNJUNGREJO KECAMATAN YOSOWILANGUN KABUPATEN LUMAJANG - Ismaul Fitroh (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2018)
Tunjungrejo is one of the unique village located in the region of Lumajang. The uniqueness of the village Tunjungrejo saw in the presence of the religion believed by locals that Protestant religion. The uniqueness of the others is their house of worship, namely East Java Christian Church (GKJW). In its development, Protestant Christianity in Tunjungrejo is the role Brontodiwirjo. Brontodiwirjo as forest loggers Tunjungrejo is also a teacher of the gospel in this region. Along Tunjungrejo forest clearing, many newcomers who are Christians and non-Christians. To maintain the existence of Protestant Christianity, Brontodiwirjo as forest loggers Tunjungrejo apply the rule that people who want to settle in the region Tunjungrejo be Protestant. From this Tunjungrejo society formed by the belief in one religion. As a result of the continued development of the Protestant Christian church, he built a house of worship that is GKJW Tunjungrejo.